Effectiveness of the APBAC Edu Model in Enhancing Critical Thinking Skills for 21st Century Learning - Mardetini, Edutivia; Dahlan, Dadang; Mulyadi, Hari; Rasto, Rasto (Lectura : Jurnal Pendidikan, 2025)
In response to the growing demand for higher-order thinking in 21st-century education, innovative learning models are needed to effectively enhance students’ critical thinking skills. This study aims to test the effectiveness of the APBAC Edu learning model in enhancing critical thinking skills. This research used a quasi-experimental approach with a pretest-posttest control group design. The population was economics education students at the Faculty of Teacher Training and Education, Sriwijaya University, and sampling used simple random sampling, 68 students Indralaya class as the experimental group using the APBAC Edu model and 27 Palembang class as the control group using the problem-based learning model. The results showed that the average score for the experimental group increased from 6.60 in the pretest to 11.60 in the posttest, achieving an N-Gain of 0.59 (59.47%), which is categorized as moderate and effective. Meanwhile, the average score of the control group increased from 7.60 to 11.80 after the intervention, N-Gain of 0.45 (45.38%), which is considered moderate and less effective. The independent sample t-test showed a significance value of 0.000 <0.05, indicating a significant difference between the two groups. In conclusion, this research confirms that the APBAC Edu and PBL models are effective in improving critical thinking skills. However, the APBAC Edu model resulted in a greater increase in average scores compared to the PBL model. Therefore, it is recommended that the APBAC Edu model be implemented in courses which aims at developing higher-order thinking skills, such as accounting practicum courses.